The structure of full-length AFPK supports the ACP linker in a role that regulates iterative polyketide and fatty acid assembly - Heidi L. Schubert; Feng Li; Christopher P. Hill; Eric W. Schmidt (Proceedings of the National Academy of Sciences, 2025)
The polyketide synthases (PKSs) in microbes and the cytoplasmic fatty acid synthases in humans (FASs) are related enzymes that have been well studied. As a result, there is a paradigm explaining in general terms how FASs repeatedly use a set of enzymatic domains to produce simple fats, while PKSs use the domains in a much more complex manner to produce pharmaceuticals and other elaborate molecules. However, most animals also have PKSs that do not conform to the rules described in microbes, including a large family of enzymes that bridge fatty acid and polyketide metabolism, the animal FAS-like PKSs (AFPKs). Here, we present the cryoelectron microscopy structures of two AFPKs from sea slugs. While the AFPK resemble mammalian FASs, their chemical products mimic those of PKSs in complexity. How then does the architecture of AFPKs facilitate this structural complexity? Unexpectedly, chemical complexity is controlled not solely by the enzymatic domains but is aided by the dynamics of the acyl carrier protein (ACP), a shuttle that moves intermediates between these domains. We observed interactions between enzyme domains and the linker-ACP domain, which, when manipulated, altered the kinetic properties of the enzyme to change the resulting chemical products. This unveils elaborate mechanisms and enzyme motions underlying lipid and polyketide biochemistry across the domains of life.